Ritual, art and/or physics? seven rare wooden oro bullroarers in the collection of the institute of african studies, University of Ibadan, Nigeria (2016)
This paper investigates the artistic characteristic features and iconology of Yoruba Oro bullroarer using selected examples of seven Oro bullroarers in the collection of the Museum of the Institute of African Studies (MIAS), University of Ibadan, Nigeria. The ethnographic research design was adopted for the study. It gathered data from in-depth interviews, historical, political, mythological, scholarly submissions and allusions on the socio-religious, cultural importance and associations of oro in Yoruba land, to elucidate traditional and contemporary perspectives about Oro and its iconography. In its conclusion, the paper highlighted the important images commonly depicted on the Oro bullroarer. Some of the images observed are zoomorphic, anthropomorphic, geometric or abstract forms. It further observes that the images on the bullroarer are purposely engineered to conform with the overall process of scientific effect of matter, energy, force and motion to produce the buzzing sound associated with Oro